Performance, risk, and cost of capital: Trends and opportunities for future CSR research - Asif Saeed; Robert Paul Sroufe (Journal of Risk and Financial Management, 2021)
The information within this study reviews the financial management literature focusing on proponents and opponents of corporate social responsibility (CSR). We review how CSR affects different areas of corporate finance. This study's core objective is to explore the last 20 years (2000-2019) of CSR top-tier literature to develop and theoretically support CSR and environmental management. Twenty years of publications provide a considerable amount of evidence on CSR's impacts on firm financial characteristics and some paradoxical findings. The majority of our insights support the argument that doing good is good for business. This study also highlights existing gaps in the literature. Based on our findings, we highlight three areas to further explore in the context of CSR and corporate finance: (1) Does CSR improve specific information contents in stock prices? (2) Does CSR mitigate financial distress risk? and (3) Is CSR good for firm trade credit?
Keywords: 330; agency; corporate social responsibility; financial performance; information environment; distress risk; trade credit